2016
DOI: 10.1371/journal.pone.0162112
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Onward Transmission of Non-Pandemic HIV-1 Subtype B Clades in Northern and Northeastern Brazilian Regions

Abstract: The Human immunodeficiency virus type-1 (HIV-1) epidemic in Brazil is mainly driven by the subtype B pandemic lineage (BPANDEMIC), while Caribbean non-pandemic subtype B clades (BCAR) seem to account for a very low fraction of HIV-infections in this country. The molecular characteristics of the HIV-1 subtype B strains disseminated in the Northern and Northeastern Brazilian regions, however, have not been explored so far. In this study, we estimate the prevalence of the HIV-1 BPANDEMIC and BCAR clades across di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 32 publications
4
26
1
1
Order By: Relevance
“…Notably, among the 73 patients included in our study and that attended the Public Health Central Laboratory in Boa Vista, two patients were from St. Helena de Uairén and one patient from Lethem, reflecting the intense human mobility across the Roraima borders with Venezuela and Guyana. Consistent with this, we recently described a singular high prevalence of non-pandemic subtype B variants of Caribbean origin in Roraima [36]. These data suggest that the HIV-1 epidemic in Roraima is more closely related to epidemics in neighboring South American countries (Venezuela and Guyana) than to epidemics in other Brazilian regions.…”
Section: Discussionsupporting
confidence: 71%
“…Notably, among the 73 patients included in our study and that attended the Public Health Central Laboratory in Boa Vista, two patients were from St. Helena de Uairén and one patient from Lethem, reflecting the intense human mobility across the Roraima borders with Venezuela and Guyana. Consistent with this, we recently described a singular high prevalence of non-pandemic subtype B variants of Caribbean origin in Roraima [36]. These data suggest that the HIV-1 epidemic in Roraima is more closely related to epidemics in neighboring South American countries (Venezuela and Guyana) than to epidemics in other Brazilian regions.…”
Section: Discussionsupporting
confidence: 71%
“…Subtype B is the predominant HIV-1 lineage circulating in French Guiana ( Kazanji et al, 2001 ; Darcissac et al, 2016 ) and Suriname ( Abdoel Wahid et al, 2016 ); but in sharp contrast to other continental American countries where the epidemic is mostly driven by the globally disseminated “B PANDEMIC ” lineage, the subtype B epidemic in French Guiana and Suriname is driven by transmission of both B PANDEMIC and of non-pandemic subtype B lineages characteristic of the Caribbean region (“B CAR ” lineages) ( Cabello et al, 2015 ). This epidemiological pattern resembles that described in several Caribbean islands (Haiti, the Dominican Republic, Jamaica, The Bahamas and the Lesser Antilles) ( Cabello et al, 2014 ) and in the Northern Brazilian state of Roraima ( Divino et al, 2016 ). Previous phylogenetic analyses revealed that a substantial fraction (30–95%) of subtype B infections in Latin American and Caribbean countries resulted from the expansion of a few local (or regional) B PANDEMIC and B CAR founder strains ( Delatorre and Bello, 2013 ; Cabello et al, 2014 , 2015 ; Mendoza et al, 2014 ; Mir et al, 2015 ; Divino et al, 2016 ), thus supporting a great geographic compartmentalization of the HIV-1 subtype B epidemic in those regions.…”
Section: Introductionsupporting
confidence: 83%
“…This epidemiological pattern resembles that described in several Caribbean islands (Haiti, the Dominican Republic, Jamaica, The Bahamas and the Lesser Antilles) ( Cabello et al, 2014 ) and in the Northern Brazilian state of Roraima ( Divino et al, 2016 ). Previous phylogenetic analyses revealed that a substantial fraction (30–95%) of subtype B infections in Latin American and Caribbean countries resulted from the expansion of a few local (or regional) B PANDEMIC and B CAR founder strains ( Delatorre and Bello, 2013 ; Cabello et al, 2014 , 2015 ; Mendoza et al, 2014 ; Mir et al, 2015 ; Divino et al, 2016 ), thus supporting a great geographic compartmentalization of the HIV-1 subtype B epidemic in those regions.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations